AN ANALYSIS OF THE READABILITY OF ENGLISH TEXTBOOKS USED BY THE STUDENTS - Nurdiana, Nurdiana; Fiprinita, Rizki; Afrizal, Afrizal; Efendi, Susmitra Muhammad (State Islamic University of Sultan Syarif Kasim Riau, 2025)
Investigating the students’ readability level of the English Textbook used in the second grade of SMK Negeri 1 Kelayang was the objective of this research. There were 25 students in the sample. This research used a content analysis method with a quantitative approach. In collecting the data, the researchers distributed a test named the Cloze test. The research finding was that the mean score of the Cloze test was 18. Based on the judgment of the students’ readability level, a score below 40 is classified as a frustration level. In conclusion, the English textbook for second-grade students of SMK Negeri 1 Kelayang is not appropriate for the students.